Aquaponik Sederhana Dalam Meningkatkan Keterampilan dan Ekonomi Masyarakat 3T - Sujarwo Sujarwo; Leo Charli; Ahmad Marsehan (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2024)
The specific objectives of implementing this service are: improving the skills of PKK mothers in Kelumpang Jaya Village through simple aquaponics, and improving the economy of PKK mothers in Kelumpang Jaya Village through simple aquaponics which not only relies on vegetable products, but also fish farming. Kelumpang Jaya village is the most extreme (front) village in Nibung sub-district. Access to the village can be done by ordering a taxi only once a day and the journey to the village takes 3 hours. Based on interviews and observations conducted with the PKK Team Leader, Mrs. Gustina Yati, apart from difficult access, this village also does not have an internet network. Difficult access and the absence of an internet network are also exacerbated by the low economy in this village, where the people of this village only work by relying on plantations in the form of rubber trees which are also far from settlements and rubber latex which no longer produces much. Even though this village is isolated with various problems, this village also has abundant natural potential, such as spacious home gardens, a variety of plants, and of course abundant water sources. The difficulty of access to the outside world also has an impact on the latest information or skills to process the natural potential we have into something that has the potential to generate and increase income. In fact, with the existing natural potential, Kelumpang Jaya Village can improve its economy with double profits.One of them is a simple aquaponics skill that combines growing vegetable plants with raising fish in one container at a time. Aquaponics is a very important cultivation technique because apart from being easy to apply and saving water, there is also an integration process with plant roots, where nitrogen waste from fish waste in the water can be reduced by being absorbed by the roots as nutrients. The results of implementing the simple aquaponics program for PKK mothers in Kelumpang Jaya Village show that there has been an increase in skills from 21% to 92%, apart from that there has also been an increase in the economy for PKK mothers in Kelumpang Jaya Village with the existence of simple aquaponics for one production generating a profit of Rp. ,98,000,-. This shows that simple aquaponics can be a new source of income for PKK mothers in Kelumpang Jaya Village